What are the effects of even-aged and uneven-aged forest management on boreal forest biodiversity in Fennoscandia and European Russia? : A systematic review - Savilaakso, Sini; Johansson, Anna; Häkkilä, Matti; Uusitalo, Anne; Sandgren, Terhi; Mönkkönen, Mikko; Puttonen, Pasi (BioMed Central, 2021)
Abstract Background Forest harvesting changes forest habitat and impacts forest dependent species. Uneven-aged management is often considered better for biodiversity than even-aged management, but there is an ongoing discourse over the benefits and disadvantages of different silvicultural systems. This systematic review contributes to the public discussion and provides evidence for policy making by synthesising current evidence on impacts of even-aged and uneven-aged forest management on biodiversity in boreal forests of Fennoscandia and European Russia. In this review even-aged and uneven-aged forest management are compared directly to each other as well as to natural forest to provide a broad basis for public discussion. Methods Both peer-reviewed and grey literature were searched in bibliographical databases, organizational webpages and internet search engines in English, Finnish, Swedish and Russian. Articles were screened for relevance by their title/abstract and again by full text. The inclusion of studies was assessed against pre-defined criteria published in an a priori protocol. A narrative synthesis and meta-analysis were conducted to describe the evidence base and to compare species richness and abundance between differently managed forests. The influence of habitat specialism, taxon, years since harvesting, deadwood availability and harvesting intensity on species richness and abundance were also tested. Review findings Searching identified 43,621 articles of which 137 articles with 854 studies had independent data and were included in the narrative synthesis. Of those, 547 studies were included in the meta-analysis. The most studied taxa were arthropods, vascular plants, bryophytes, fungi, and lichens. Results showed that forests with less disturbance (uneven-aged and mature even-aged) host more forest dependent species than young even-aged forests (< 80 years old) although the difference was only marginally significant for mature even-aged forests (> 80 years old). Uneven-aged forest had ...